Management of bleeding in patients treated with oral antithrombotic therapy - Zydek, B.; Lindhoff-Last, E. (Phlebologie, 2018)
The worldwide increase in the aging population and the associated increase in the prevalence of atrial fibrillation and venous thromboembolism as well as the widespread use of direct oral anticoagulants (DOAC) have resulted in an increase of the need for the management of bleeding complications and emergency operations in this group of patients, in clinical practice. When severe bleeding occurs, general assessment should include evaluation of the bleeding site, onset and severity of bleeding, renal function and concurrent medications with focus on antiplatelet drugs and nonsteroidal anti-inflammatory drugs (NSAID). The last intake of the DOAC and its residual concentration are also relevant. The site of bleeding should be immediately localized, anticoagulation should be interrupted, local measures to stop bleeding should be taken. Immediate reversal of the antithrombotic effect may be indicated. If relevant residual DOAC-concentrations are expected and surgery cannot be postponed, prothrombin complex concentrate (PCC) and/ or a specific antidote should be given. As a specific antidote for dabigatran, idarucizumab is available, while andexanet alfa, an antidote for the reversal of inhibitors of coagulation factor Xa, has been approved in May 2018 for clinical use only in the USA.
Keywords: Direct oral anticoagulants; life-threatening bleeding; emergency operation; Antidotes